Answer:
Step-by-step explanation:
F(x)=-x+5
So
f(-4)= -(-4)+5
f(-4)= 4+5
f(-4)= 8
Only we have to substitute value of x then after simplification we will get answer..Hope this will help
Answer: the solutions to the system of equations are x = 2 and x = 1
Step-by-step explanation:
The system of equations given equation is
y = 3x - 2 - - - - - - - - - - 1
y = x^2 - - - - - - - - - - - - 2
Substituting 1 into equation 2, it becomes
x^2 = 3x - 2
x^2 - 3x + 2 = 0
We would apply the method of factorization in solving the equation. We will get two numbers such that when added, the result would be - 3x and when multiplied, the result would be 2x^2. The numbers are - 2x and - x. It becomes
x^2 - 2x - x + 2 = 0
x(x - 2) - 1(x - 2) = 0
(x - 2)(x - 1) = 0
x - 2 = 0 or x - 1 = 0
x = 2 or x = 1
.
Answer:
x^2+y^2=d^
Step-by-step explanation:
Answer:
Step-by-step explanation:
break it down as many times as you can. how? just keep dividing each by 2. example: 85 divided by 2 is 42.5 so under both arrows put 42.5. then divide that by 2. 42.5 divided by 2 is 21.25. keep dividing until you cant no more